2021
DOI: 10.1109/access.2021.3065412
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Customizable Services for Multimodal Smart Mobility With City-Platforms

Abstract: In the last decades, the cities' capacity for generating digital information has grown exponentially. In this context, the successful implementation of smart cities' concept depends on the current possibility of handling the significant volumes of sensed data. This is particularly notorious in the case of urban mobility. Researchers in the field of urban planning have shown a great interest in urban mobility problems, proposing different route recommendation services towards making it easier and safer to move … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 66 publications
(59 reference statements)
0
17
0
Order By: Relevance
“…The model of the smart city community seems to follow the general form of the model. This is a trend towards more sophisticated intersections, clustering, and deep learning models [145][146] [147]. Some authors observed the energy utilizations and the indoor comfort with exceptionally powered information utilizing IoT innovation.…”
Section: Smart Energy Management System In Smart Homesmentioning
confidence: 99%
“…The model of the smart city community seems to follow the general form of the model. This is a trend towards more sophisticated intersections, clustering, and deep learning models [145][146] [147]. Some authors observed the energy utilizations and the indoor comfort with exceptionally powered information utilizing IoT innovation.…”
Section: Smart Energy Management System In Smart Homesmentioning
confidence: 99%
“…Wireless sensor network technologies provide both the means of communication and the corresponding infrastructure. To obtain and integrate information from sensors and provide aggregated and intelligent views of raw data, the development of integration platforms is needed [83]. The literature frequently implicitly assumes that data are real-time, openly available, of good quality, and consumable.…”
Section: Thematic Analysis 421 Technical Systemmentioning
confidence: 99%
“…Sustainability 2023, 14, x FOR PEER REVIEW 9 of 21 sensors and provide aggregated and intelligent views of raw data, the development of integration platforms is needed [83]. The literature frequently implicitly assumes that data are real-time, openly available, of good quality, and consumable.…”
Section: Thematic Analysis 421 Technical Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…and enables dynamic collaborations among users, such as crowdshipping [4] or crowdsensing [5,6] scenarios. In a multimodal context [7,8], real-time recommendation systems may suggest any type of appropriate means of transport (not just bikes) that fits the particular needs and preferences of a user at a particular moment. In some cases, this may alleviate the quality of service problems within a BSS due to imbalances, as mentioned above.…”
Section: Introductionmentioning
confidence: 99%